Deformation and failure of pseudo-ductile quasi-isotropic all-carbon hybrid FRPS with an open hole under tension. (15th May 2022) - Sapozhnikov, S.B.; Lomov, S.V.; Swolfs, Y.; Carvelli, V.
Abstract: An experimental study has been carried out to investigate the elastic and pseudo-ductile deformation processes of carbon fibre reinforced plastics, containing low elongation (LE) and high elongation (HE) layers of standard thickness. The behaviour of unidirectional homogeneous LE- and HE-laminates, hybrid [HE/LE/HE] and quasi-isotropic composites, with sublaminates sequence [0/45/90/-45]s and [0/60/-60]s were studied up to complete tensile failure. Tests carried out on standard prismatic specimens and specimens with a central hole. A clip-on extensometer and digital image correlation (DIC) were used to distinguish the stable elastic deformation, the microdamage accumulation in the LE-layers, and the delamination of LE and HE layers. For notched specimens, acoustic emission signals revealed the accumulation of scattered microdamage and the localisation of the pseudo-ductility around the hole. The quasi-isotropic hybrid laminates were almost notch insensitive, with the notch sensitivity factors in the open hole tension test for pseudo-yield and ultimate stress below 1.15.